Ulcerative Lichen Planus in Childhood - Chiyadu Padmini; K. Yellamma Bai; Vinil Chaitanya; M. Shilpa Reddy (Case Reports in Dentistry)
Lichen planus (LP) is a chronic inflammatory mucocutaneous condition which is relatively common in adults but rarely affects children. The present study is a report on an unusual case of ulcerative oral LP involving the dorsum of tongue in a 12-year-old boy. Patient complained of painful oral lesion on the tongue which was burning in nature and obstructing talking and eating spicy foods. On intraoral examination, a white ulcerative lesion on the dorsum of tongue was observed. Diagnosis was made based on clinical examination and histopathological features. We instituted local treatment and patient responded well to the treatment. Although rarely reported in childhood, lichen planus should be considered in a differential diagnosis of hyperkeratotic, reticular, and ulcerative lesions of the oral mucosa in children.